Radiological and clinical outcomes of using Chartis to plan endobronchial valve treatment - Herth, Felix; Eberhardt, Ralf; Gompelmann, Daniela; Ficker, Joachim H.; Wagner, Manfred; Ek, Lars; Schmidt, Bernd; Slebos, Dirk-Jan (The European respiratory journal, 2013)
One-way endobronchial valves (EBVs) have been shown to relieve symptoms of emphysema, particularly in patients without collateral ventilation (CV) between the target and adjacent lobes. In this study, we investigated the ability of the bronchoscopic Chartis™ Pulmonary Assessment System to predict treatment response by determining the presence of CV. - 80 EBV patients underwent a pre-treatment Chartis assessment. Before and 30 days after implantation, high-resolution computed tomography scans were taken to determine target lobe volume reduction (TLVR). A pre- to post-treatment reduction of ≥350 mL was defined as significant. In addition, clinical outcomes (forced expiratory volume in 1 s (FEV1), 6-min walk test and St George’s Respiratory Questionnaire) were compared over the same time period. - Of the 51 patients classified as having an absence of CV according to their Chartis reading, 36 showed a TLVR ≥350 mL. 29 patients were classified as having CV, and of these 24 did not meet this TLVR cut-off. Chartis showed an accuracy level of 75% in predicting whether or not the TLVR cut-off would be reached. Those predicted to respond showed significantly greater TLVR (p<0.0001) and FEV1 improvement (p=0.0013) than those predicted not to respond. - Chartis is a safe and effective method of predicting response to EBV treatment.